PENENTUAN RUTE PADA SISTEM DISTRIBUSI PRODUK - Suci Oktri Viarani M; Ahmad Syafruddin I; Wahyu Fitrianda Mufti (Politeknik ATI Padang, 2019)
PT. X is a distributor of beverage companies that produces various soft drinks (soft drinks). The problem that occurs in these distributors is that they have to service many shops located far from warehouses, with locations scattered in several places and limited transportation facilities with an average capacity of 150 boxes / car. The average number of stores that must be visited every day is 40 for one distribution area. Planning the sequence of product distribution to consumers is still based on subjective decisions from the driver and kernet, so the product distribution time is less than the maximum. This research will design a product delivery route applying the Traveling Salesman Problem (TSP) model to optimize the distribution route. This research uses store sorting method namely Nearest Neighbor and Branch and Bound methods with the help of WinQSB software so that the best product delivery route is obtained. These results can be seen with more optimal mileage, travel time and costs. Based on data processing, it was found that the best X product delivery route at the distributor of PT X Bukittingi was obtained using the Branch and Bound store ordering method.